Technical Meditation and The Fire War: some considerations and approaches (Research, Society and Development, 2020)
In this text we present a review of the book Meditação da Técnica, by Ortega y Gasset who, in 1963, decided to publish his class notes of a course that the author taught on the subject at the International University of Summer of Santander. We also used the 1981 film The War of Fire, directed by Jean-Jacques Annaud, as the guiding thread of approximations and reflections about the book in question.